Study of Productivity Results of Bottom Trap Capture Using Different Attractors on Poncan Island, Tapian Nauli Bay, Sibolga City - Afni Afriani; Ladestam Sitinjak (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The bottom trap is one of the traps that is designed in the form of a cage with a cylindrical funnel sothat fish can easily enter and are difficult to escape. The purpose of the study was to determineproductivity level of bottom trap catches using different attractors, knowing the diversity of typesof bottom trap catches and the most effective attractor types to the catch. The method used isexperimental fishing with three basic trap units and three fishing trips with areca nut, coconutleaves and without attractor. The result showed that that highest productivity of the catch during thestudy was in area leaf attractor with total 39, followed by the coconut leaf attractor with total of 25individuals, and not attractor with an average 19 individuals. Types of fish caught consistedPompano (Carangidae), red grouper (Chapalapholis uredeta), Estuarine grouper (Ephinepeluscoioides), red snapper (Lutjanus malabaricus), and lionfish (Pterois volitans). Total number offish caubht by bottom traps shows F count > Ftable. Conclusions obtained from this reseach,Different attaractors have a significant effect on the catch.